Razões que levaram os consumidores de energia elétrica a se transformarem em geradores : uma análise da geração fotovoltaica na cidade de Vitória-ES - Oliveira Junior, Luiz Guilherme (2018)
With the entry into force of ANEEL Normative Resolution No. 482/2012 (supplemented by ANEEL Normative Resolution No. 687/2015) and with the creation of the Electric Energy Compensation System (the national mechanism of Net Metering), it has emerged, in Brazil, the possibility of the consumer generating their own electricity through renewable sources (distributed generation of small scale), having as support a defined and unbureaucratic regulatory space. It´s a model that is glimpsed to attract environmental and social benefits because it is based on small electric power generation projects, which in turn can induce more sustainable consumption patterns. In this context, identify and analyze the reasons that led the electric power consumers to become solar photovoltaic generators, despite the economic and financial unfeasibility of projects, will contribute to decisions of future micro and mini-generators in order to opt for this generation. The methodology used was based on bibliographical and documentary research and the objectives achieved through a research questionnaire applied to 26 Consumer Units listed at ANEEL as generators of their own electricity through Photovoltaic Generating Units in the city of Vitória, Espírito Santo state. The work leaves a contribution of propositions of propositions to the sector of distributed generation (DG) and analyzes the present public policies. It was concluded that even if DG is not part of a consolidated and strategic policy; lack of knowledge of the Resolution itself and other direct incentives, photovoltaic generators are satisfied with the system, but have not installed it due only to seeking a reduction in the value of their electricity bills and access to fiscal and regulatory incentives, but rather to sustain their beliefs from the environmental point of view.